Preparation, structure and properties of litchi pericarp polysaccharide - Yijie Wang; Gangliang Huang (Scientific Reports)
Abstract A high purity polysaccharide (UELPP-A1) was isolated from the crude polysaccharide of litchi pericarp (UELPP) by column chromatography, and acetylated polysaccharide (AC-UELPP) was obtained by acetylation modification of the crude polysaccharide of litchi pericarp. The physicochemical properties and in vitro antioxidant activity of UELPP-A1 and AC-UELPP were compared. The C/H on UELPP-A1 was assigned by Congo red test, FTIR, 1D and 2D NMR, and its structural characteristics were characterized. The results showed that the total sugar content of neutral UELPP-A1 was significantly increased to 94.15%, and its structure did not have a triple helix structure. In addition, the in vitro antioxidant activity test showed that both polysaccharides had antioxidant activity in a dose-dependent manner. The enhancement effect of AC-UELPP with the increase of concentration was the most significant (P < 0.05). Among them, the hydroxyl radical scavenging activity was stronger than its reducing ability and superoxide anion radical at the same polysaccharide concentration. Acetylation modification can improve the antioxidant activity of UELPP and has further research value for human health care.